2017
DOI: 10.4236/oje.2017.72009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two <i>Trichogramma</i> Species with <i>Bacillus thuringiensis</i> var. krustaki for the Control of the Tomato Leafminer <i>Tuta absoluta</i> Meyrick (Lepidoptera: Gelechiidae) in Iran

Abstract: In this study, we investigated the efficiency of T. brassicae and T. embryophagum in combination with bacterial suspension of B. thuringiensis against the tomato leafminer T. absoluta eggs in cage inside greenhouse (semi field) experiments. Four treatments were used (T. brassicae or T. embryophagum + T. absoluta) (T1), (B. thuringiensis + T. absoluta) (T2), (T. brassicae or T. embryophagum + B. thuringiensis + T. absoluta) (T3) and control (T4). The lowest number of T. absoluta mines (6.1, 0.5 mine per plant) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In support of these considerations, different studies showed that the integration of B. thuringiensis with Trichogramma spp. egg parasitoids (Hymenoptera: Trichogrammatidae) significantly decreased T. absoluta infestations in field conditions [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…In support of these considerations, different studies showed that the integration of B. thuringiensis with Trichogramma spp. egg parasitoids (Hymenoptera: Trichogrammatidae) significantly decreased T. absoluta infestations in field conditions [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive and uncontrolled use of these pesticides aggravates resistance problems over abamectin, cartap, methamidophos, and permethrin (Victor & Mwangi, 2019). Current investigations show that T. absoluta is impervious to the wide scope of pesticides including chlorantraniliprole, abamectin, deltamethrin, methamidophos, permethrin, cartap in Argentina, Brazil, South Africa, and chile (Alsaedi et al, 2017;Hogea, 2020;Jac, 2017) (Table 7). Howsoever, some pesticides are as yet viable against T. absoluta including Chlorantraniliprole, Emamectin benzoate, Imidachloprid, spinosad, indoxacarb, spinetoram, Novaluron, flubendiamide, dichlorovus (Bastola et al, 2020;Huda et al, 2020;Khani et al, 2020;Wakil et al, 2018).…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Combined releases of the parasitoid T. evanescens and the predatory mirid N. tenuis proved to reduce fruit infestation in greenhouse tomatoes in the western Mediterranean region of Turkey (Keçeci and Oztop 2017). Similarly, releases of Trichogramma embryophagum (Hartig) parasitoids (20 adults per plant) along with Bt application or release of Trichogramma brassicae (Bezdenko), combined with spinosad spraying, significantly decreased T. absoluta densities and leaf mines in Iranian greenhouse tomato crops (Alsaedi et al 2017;Jamshidnia et al 2018).…”
Section: Egg Parasitoidsmentioning
confidence: 98%